(untitled) (Significação: Journal of Audiovisual Culture, 2021)
The article deals with how Arlindo Machado’s work establishes the main reading field of video arts in Brazil, specially in two articles, A experiência do vídeo no Brasil and As linhas de força do vídeo brasileiro, which, despite the importance of its contribution, has not yet been systematically discussed. To this end, a critical reading of Machado’s thought is made, as it appears in his main books. Consequently, we conclude that Machado’s work contributes to the formation of a research field that proposes a critical reading of technical images, which the author does in two complementary ways: by dismantling established languages and by mapping emerging languages.